2022
DOI: 10.1136/jitc-2022-005308
|View full text |Cite
|
Sign up to set email alerts
|

Tumor MHC class I expression alters cancer-associated myelopoiesis driven by host NK cells

Abstract: Downregulation of MHC class I (MHCI) molecules on tumor cells is recognized as a resistance mechanism of cancer immunotherapy. Given that MHCI molecules are potent regulators of immune responses, we postulated that the expression of MHCI by tumor cells influences systemic immune responses. Accordingly, mice-bearing MHCI-deficient tumor cells showed reduced tumor-associated extramedullary myelopoiesis in the spleen. Depletion of natural killer (NK) cells abrogated these differences, suggesting an integral role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…However, the underlying trigger that initiates the production of IL-6 by NK cells remains unknown. Recent studies revealed that defective NK cell cytotoxicity is associated with the increased production of inflammatory cytokines (61)(62)(63). Still, the underlying cellular biology in which cytokine production is mechanistically influenced by NK cell-killing capacity remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the underlying trigger that initiates the production of IL-6 by NK cells remains unknown. Recent studies revealed that defective NK cell cytotoxicity is associated with the increased production of inflammatory cytokines (61)(62)(63). Still, the underlying cellular biology in which cytokine production is mechanistically influenced by NK cell-killing capacity remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our b2m -KO tumor models, Bunting et al ( 62 ) demonstrated that MHCI expression in melanoma is associated with the deposition of extracellular proteins that dampen NK cell–killing capacities and promote their production of inflammatory cytokines. NK cells within MHCI-deficient RMA-S lymphoma tumors were also found to produce higher amounts of IFN-γ ( 63 ). By either knocking out B2M in murine tumor cells or depleting the host NK cells, the frequencies of M-MDSCs in the tumors were also reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of gut microbiota on tumor immunity is similar to that of irAEs in terms of antigenicity. It is noteworthy that the administration of antibiotics before IOs has been shown to disrupt the gut microbiota and subsequently reduce the incidence of irAEs (Kostine et al 2021 ; Neo et al 2022 ). Certain bacterial species, such as Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%